Implementation of specific interventions for the 1st 1000 days of life to prevent stunting in Padang city during the COVID-19 pandemic - Fadhil, Muhammad; Djafri, Defriman; Masnarivan, Yeffi (BKM Public Health and Community Medicine, 2021)
​​Objectives: Covid-19 pandemic affected all sectors, including health. Stunting prevalence in Indonesia by 2019 is 26.67%, above 20% of Indonesia’s target. This study aims to review the implementation of specific interventions for the 1st 1000 days of life to prevent stunting in Padang City during Covid-19 Pandemic. Method: The design in this study uses mixed methods. This study took place in August 2020 – February 2021 at two health centers (Belimbing and Seberang Padang). A systemic approach was made for a qualitative method, and there were 11 informants required in this study determined by purposive sampling. Data collection uses in-depth interviews, observations, and document review, with data source and method triangulation. The quantitative method was analyzed using univariate analysis to observe the differences in 2019 and 2020 specific interventions for stunting. Result: This pandemic affected two study health centers. Most interventions did not reach their targets, such as exclusive breastfeeding, complete basic immunization, health promotion activities, vitamin A and folic acid intake, and pregnancy visits to healthcare facilities. Puskesmas Seberang Padang distinguished Covid-19 task force and stunting interventions team, and in Puskesmas Belimbing add more days for immunization. Diarrheas increased from 92 to 101 cases in 2018 and 2019 at Seberang Padang, while decreased from 101 to 56 cases at the Belimbing. Conclusion: Both health centers have different strategies and priorities for tackling stunting during the Covid-19 pandemic. In short, many interventions did not reach the target. The trend of diarrheal in 2018 and 2019 at Puskesmas Seberang Padang decreased and increased at Puskesmas Belimbing. Both health centers need to maximize the intervention for stunting during the Covid-19 pandemic by sticking to health protocols.